Dinamika komunikasi gabungan kelompok tani (gapoktan) sumber rezeki dalam mendukung program ketahanan pangan di Desa Bungaraya Kabupaten Siak - Mulyasara, Anis; Anti, Titi (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: Bungaraya District is one of the largest rice producing areas in Riau Province. However, in 2023 there will be a decrease from the total target of 45,463 tons to 26,064 tons. Findings: So of course it needs to be supported by the food security program implemented by Gapoktan. This research aims to describe the dynamics of communication that occur within Gapoktan Sumber Rezeki in supporting the Food Security program. Methods: This research uses descriptive qualitative research methods with a total of 7 informants. Conclusion: The research results show that the dynamics of communication in Gapoktan are divided into Vertical Communication and Horizontal Communication. Vertical Communication occurs formally through meetings to discuss food security programs. Horizontal communication occurs formally through meeting activities both in the office and in the field. Then, non-formal communication occurs when members chat casually in the rice fields/fields. Overall, formal and non-formal communication has an important role at Gapoktan Sumber Rezeki in establishing relationships between members or between Gapoktan and PPL in supporting the Food Security Program. So it can be seen that the communication process that occurs supports the food security program.